Obesity in multiracial schizophrenia patients receiving outpatient treatment in a regional tertiary hospital in Malaysia - A.Talib, Norlelawati; Abdullah, Kartini; Musa, Ramli; Ku Zaifah, Norsidah; Wan Sulaiman, Wan Azizi; Abdul Razak, Tariq (Hong Kong College of Psychiatry, 2012)
OBJECTIVES. Obesity is an issue of concern among patients with schizophrenia as it is a co-morbid condition that is closely related to metabolic syndrome. The present study assessed the correlation of body mass index with antipsychotic use among multiracial schizophrenia outpatients. The study also compared the patients' body mass index with Malaysian Adult Nutrition Survey (MANS) data. METHODS. A total of 216 participants were recruited into a cross-sectional study conducted over 5 months, from December 2010 to April 2011. Body weight and height were measured using the standard methods. Demographic data and treatment variables were gathered through interview or review of the medical records. RESULTS. There were differences in mean body mass index between men and women (p = 0.02) and between Malay, Chinese and Indian races (p = 0.04). Stratified by sex, age, and race, the body mass index distributions of the patients were significantly different to those of the reference MANS population. The prevalence of obesity among patients was more than 2-fold greater than among the reference population in all variables. Although body mass index distribution was related to antipsychotic drugs (χ(2) = 33.42; p = 0.04), obesity could not be attributed to any specific drug. CONCLUSION. The prevalence of obesity among patients with schizophrenia was significantly greater than that in the healthy Malaysian population, and affects the 3 main races in Malaysia.